Temporal and spatial requirement of EMF1 activity for arabidopsis vegetative and reproductive development - Sanchez, Rosario; Calonje, Myriam (Molecular plant, 2009)
EMBRYONIC FLOWER (EMF) genes are required to maintain vegetative development via repression of flower homeotic genes in Arabidopsis. Removal of EMF gene function caused plants to flower upon germination, producing abnormal and sterile flowers. The pleiotropic effect of emf1 mutation suggests its requirement for gene programs involved in diverse developmental processes. Transgenic plants harboring EMF1 promoter::glucuronidase (GUS) reporter gene were generated to investigate the temporal and spatial expression pattern of EMF1. These plants displayed differential GUS activity in vegetative and flower tissues, consistent with the role of EMF1 in regulating multiple gene programs. EMF1::GUS expression pattern in emf mutants suggests organ-specific auto-regulation. Sense- and antisense (as) EMF1 cDNA were expressed under the control of stage- and tissue-specific promoters in transgenic plants. Characterization of these transgenic plants showed that EMF1 activity is required in meristematic as well as differentiating tissues to rescue emf mutant phenotype. Temporal removal or reduction of EMF1 activity in the embryo or shoot apex of wild-type seedlings was sufficient to cause early flowering and terminal flower formation in adult plants. Such reproductive cell memory is reflected in the flower MADS-box gene activity expressed prior to flowering in these early flowering plants. However, temporal removal of EMF1 activity in flower meristem did not affect flower development. Our results are consistent with EMF1’s primary role in repressing flowering in order to allow for vegetative growth.